Pandangan Islam terhadap Fundamentalisme: Analisis Tafsir Maudhu’i - Farhan Bahrul Ulum; Kholid Nurrohman; Fahad Fauzi; Hana Mariatul Qibtiyah; Asep Abdul Muhyi (Gunung Djati Conference Series, 2023)
This research aims to get to know Islam and Fundamentalism. This research is qualitative research with a descriptive method and maudhu`i interpretation. This type of qualitative approach is based on secondary data sources which are literature related to the topic of this research originating from journal articles, books, and others. Data analysis techniques are taken through the stages of inventory, classification, and interpretation. The technique of checking the validity of the data is carried out by means of library research. The research results obtained indicate that there are several findings that the author obtained, namely, among others, a description of the concept of fundamentalism, fundamentalism and religion, how the history of the birth of fundamentalism, several problems of Islamic fundamentalism, and the results of research on verses of the Qur'an with maudhu`i interpretations related to Islamic fundamentalism.